Capital Structure, Investment Opportunity Set, and Corporate Social Responsibility as Determinants of Firm Value in Indonesian State-Owned Enterprises - Yayu Kusdiana; Arie Yusnelly; Muhammad Firmansyah; Tran Thai Ha Nguyen (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
This study examines the effect of Corporate Social Responsibility (CSR), Investment Opportunity Set (IOS), and Capital Structure on the firm value of State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX) during the 2018–2022 period. Firm value represents investors’ assessment of a company’s future prospects and sustainability, particularly for SOEs that carry both economic and social responsibilities. This research adopts a quantitative approach with a causal research design, utilizing secondary data derived from published financial and annual reports. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to evaluate both the measurement and structural models. The findings reveal that the Investment Opportunity Set (IOS) has a positive and significant effect on firm value, indicating that growth opportunities and future investment prospects are strongly considered by investors in valuing SOEs. In contrast, Corporate Social Responsibility (CSR) and Capital Structure do not show a significant direct effect on firm value. These results suggest that market participants place greater emphasis on growth potential rather than on leverage decisions or CSR disclosures in assessing SOE performance. The model explains a substantial proportion of the variance in firm value, indicating that IOS, CSR, and Capital Structure jointly contribute to explaining firm valuation, although other factors beyond the model also play a role. This study contributes to the literature by providing empirical evidence on the determinants of firm value in Indonesian SOEs, highlighting the dominant role of growth opportunities in shaping market perception. The findings offer practical implications for policymakers and SOE management in formulating strategic financial and investment policies to enhance firm value.